2010
DOI: 10.1016/j.atherosclerosis.2009.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium and prognosis in cardiovascular disease: results from the AtheroGene study

Abstract: Objective-Experimental data suggest a protective role of the essential trace element selenium against cardiovascular disease (CVD), whereas epidemiological data remains controversial. We aimed to investigate the impact of serum selenium concentration in patients presenting with stable angina pectoris (SAP) or acute coronary syndrome (ACS) on long term prognosis.Methods-Baseline selenium concentration was measured in 1731 individuals (852 with SAP, and 879 with ACS). During a median follow-up of 6.1 years, 190 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 27 publications
0
43
0
2
Order By: Relevance
“…Although it appears that selenium supplementation has no effect on CVD risk in healthy individuals, in a very recent AtheroGene study, low selenium concentration was associated with future cardiovascular death in patients with acute coronary syndrome, although no effect on stable angina pectoris (232). Further, in the selenium Therapy in Coronary Artery disease Patients (SETCAP) Study, supplementation of sodium selenite increased GPx1 activity in endothelial cells and in coronary artery disease (CAD) patients.…”
Section: A Cardiovascular Diseasementioning
confidence: 97%
“…Although it appears that selenium supplementation has no effect on CVD risk in healthy individuals, in a very recent AtheroGene study, low selenium concentration was associated with future cardiovascular death in patients with acute coronary syndrome, although no effect on stable angina pectoris (232). Further, in the selenium Therapy in Coronary Artery disease Patients (SETCAP) Study, supplementation of sodium selenite increased GPx1 activity in endothelial cells and in coronary artery disease (CAD) patients.…”
Section: A Cardiovascular Diseasementioning
confidence: 97%
“…Data from many studies about the associations between selenium and cardiometabolic risk factors were inconsistent. Previous populationbased studies have reported inverse correlations between serum selenium levels and cardiovascular mortality [13,39]. Obeid et al reported that there was a positive correlation between plasma selenium levels and all the components of metabolic syndrome [40].…”
Section: Discussionmentioning
confidence: 98%
“…Selenium is also an essential mineral that plays an important role in the antioxidant defense by participating in the structure of selenocysteine and glutathione peroxidase enzymes [12]. Several studies have reported association between low selenium concentrations and increased risk of cardiometabolic disease [13].…”
Section: Introductionmentioning
confidence: 99%
“…2 It has been reported that, Se and GSHPx participate in epilepsy pathogenesis. 3 The immuno-enhancing 4,5 , anti-viral [6][7][8] , cancer prevention 9-13 effects of Se, the protective role of Se against radiation, 14,15 cardiovascular diseases, 16,17 and reproductive disorders 18,19 have also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%